Declaration of the international pediatric association on the conditions of child detention facilities at the borders of the United States Of America - Errol Alden; Naveen Thacker (Педиатрическая фармакология)
The International Pediatric Association, devoted to the well-being of children across the globe and composed of 169 national, regional and subspecialty pediatric societies representing over one million pediatricians, caring for more than one billion children, issues the following declaration